Analisis Nilai Pendidikan Dalam Tafsir Ibnu Katsir Juz 21 Karya Dr. Abdullah Bin Muhammad ‘Alu Syaikh - Kasmanah (CBJIS: Cross-Border Journal of Islamic Studies, 2022)
The purpose of this research was to find the educational values ​​contained in the Tafsir Ibnu Katsir Juz 21 by Dr. Abdullah bin Muhammad 'Alu Shaykh. The method used in this type of qualitative research is content analysis techniques. The data were obtained through identification based on a structural analysis approach from the translated text in Tafsir Ibnu Katsir Juz 21, which consists of 5 letters consisting of 180 verses. That is QS. Al-Ankabut, Ar-Rum, Luqman, As-Sajdah, and Al-Ahzab. Based on the research findings in Tafsir Ibnu Katsir Juz 21 contains educational values ​​as much as 186 verses, 19 verses in the form of intellectual education values, 4 verses in the form of aesthetics, 31 verses in the form of moral education values, 127 verses in the form of religious education, 1 verse in the form of social education, 1 verse in the form of citizenship education, 3 verses in the form of physical education. Meanwhile, the value of skills education was not found in this analysis. As for the interpretation of the analyzed data, it can be concluded that the value of religious education is in the form of aqidah or belief in God as God who created the universe in everything. Meanwhile, the value of intellectual education describes the knowledge of the process of its creation. The creation is perfected in a form that is beautifully described in a verse which contains the value of aesthetic education. The physical strength of humans as a result of the perfection is explained in the verse which contains the value of physical education. Manners and human behavior are described in several verses which contain the value of moral education. The scope of human life in communicating between fellow and state is described in a verse which contains the value of social education and citizenship.